Long Term Health Problems and Associated Factors among COVID-19 Recovered Patients (Community Based Medical Journal, 2024)
A cross-sectional, descriptive study was conducted among 181 individuals recovered from COVID-19 infection and had been missing infection (negative rt-PCR test) or signs-symptoms for minimum three months. The study aims determine newly developed health problems in patients, which was conducted at Post-COVID Unit of Anwer Khan Modern Medical College Hospital, Dhaka, Bangladesh, between July 2021 and June 2022. Through convenient sampling, data were collected by face-to-face interview and history of signs/ symptoms during the infection were recorded from reviewing prescription and interview as well by using a semi-structured questionnaire. The mean age of the participants was 39.56±6.92 years and male-female ratio was 1.45:1. The mean monthly family income of the participants was 36,022.09±4130.56 BDT which represents lower middle to middle class family in terms of Bangladesh context. During COVID-19 infection most of the (97%) respondents had fever, and 87%, 79% of the patients had sore throat and cough respectively as common symptoms; in addition, more than one-third (34%) had diarrhea. Several constitutional symptoms also recorded during their course of illness like headache (74%) and malaise (54%). More than one-third (34%) of the respondents required admission in hospital. During the course of infection, 41%, 26% and 31% participants were suffered from mild, moderate and severe form of COVID-19 illness. Most of the respondents developed long term health problems following COVID infection and post-viral fatigue was the most prevalent (85%) among the post COVID individuals and this long-term health problem-post viral fatigue was found to be associated with monthly income and it was statistically significant (p